Price shocks and the components of urban inflation - Clark, G (Pion Ltd., 1984)
In a previous study of US city inflation, I emphasized the temporal regularities of urban price inflation. But, despite these identified regularities, it is apparent that the process of inflation is rarely so regular and so systematic. Unanticipated shocks in three components, energy food, and housing, dominate the post-1950 record of US inflation. Analysis of specific events and the patterns of local inflation in these three components reveals that food shocks and, to a lesser extent, energy price shocks have had relatively even spatial repercussions. However, it is also apparent that housing price inflation has varied considerably over space and time. Even so, it is still plausible that national price inflation is a fair approximation for local inflation.